Communicating Hospitality: A Speech Act Analysis of Tourism Services at Lake Toba - Taulia; Gapur, Abdul; Pujiono, Mhd (International Journal of Culture and Art Studies, 2024)
As a national super-priority tourist attraction, Lake Toba must improve several facets of its tourism services, particularly the communicative practices of tourism service providers. This research examines speech actions within the linguistic register of tourism services in the Lake Toba region. In this research setting, comprehending linguistic elements and language registers, particularly pragmatics, is essential for advancing the Lake Toba tourism region. The research employs Austin and Searle's speech act theory to delineate speech acts. The dataset comprises speech actions from tourism services in Lake Toba, derived from three sectors: souvenir shops, lodging, and dining establishments. This research will significantly enhance the tourism industry in Lake Toba by providing insights that improve communication quality and tourism services, while reducing potential communication obstacles. The findings identify three primary categories of speech actions in Lake Toba's tourism services according to the theories of Austin and Searle: locutionary, illocutionary, and perlocutionary acts. Locutionary acts provide fundamental information or pose inquiries, illocutionary acts include requests or directives for prompt action, and perlocutionary acts emphasize the consequences of communication. The roles of these speech acts—issuing commands, granting permits, offering ideas, and making requests—are essential for efficient service delivery and improving the tourism experience.